2001
DOI: 10.1068/p3030
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity and the ‘Mental Eye’ in Pictorial Relief

Abstract: Photographs of scenes do not determine scenes in the sense that infinitely many different scenes could have given rise to any given photograph. In psychophysical experiments, observers have (at least partially) to resolve these ambiguities. The ambiguities also allow them to vary their response within the space of 'veridical' responses. Such variations may well be called 'the beholder's share' since they do not depend causally on the available depth cues. We determined the pictorial relief for four observers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
173
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(181 citation statements)
references
References 9 publications
7
173
1
Order By: Relevance
“…It follows that, if neither is zero, they can both be positive (the surface is locally convex), both negative (locally concave), or one positive and one negative (saddle shaped). Koenderink (1984; see also Koenderink & van Doorn, 1982;Koenderink, van Doorn, Kappers, & Todd, Fig. 1 The C-shape on the left has a contour that changes in curvature, positive on the outside and negative on the inside.…”
Section: Questionmentioning
confidence: 99%
“…It follows that, if neither is zero, they can both be positive (the surface is locally convex), both negative (locally concave), or one positive and one negative (saddle shaped). Koenderink (1984; see also Koenderink & van Doorn, 1982;Koenderink, van Doorn, Kappers, & Todd, Fig. 1 The C-shape on the left has a contour that changes in curvature, positive on the outside and negative on the inside.…”
Section: Questionmentioning
confidence: 99%
“…Summary: Koenderink and colleagues compared these three tasks [17]. Coherent results can be achieved across observers and tasks.…”
Section: Psychophysical Experimentsmentioning
confidence: 99%
“…The works of Koenderink et al [17] and Todd [34] describe the three most frequently employed experiments for probing perceived surfaces.…”
Section: Psychophysical Experimentsmentioning
confidence: 99%
“…Previous research has shown that differences concerning depth maps between participants could be ruled out by affine transforming the depths of one participant into the depths of the other participant (Koenderink et al, 2001). We were curious whether affine regression would here, too, have more predictive power than just straight regression.…”
Section: Global Differencesmentioning
confidence: 99%
“…The shears between the pictorial reliefs of the original and the mirrored pictures obtained for the different participants can be compared by depicting them in a polar coordinate representation (Figure 8). In this figure, the global shear determined by the weights of the image coordinates in the regression model (see also Koenderink, van Doorn, Kappers, & Todd, 2001) is presented for each pose and for each participant. The shears for OR-LR are generally very small.…”
Section: Global Differencesmentioning
confidence: 99%